China and Sukarno’s nuclear ambitions : translated and annotated documents from the Chinese foreign ministry archives - Zhou, Taomo (2020)
Inspired by China’s 1964 demonstration of its nuclear capability, Indonesian President Sukarno attempted to direct Indonesia’s nuclear program toward military use. Sukarno’s openly expressed nuclear ambition shocked foreign leaders and officials and created a longstanding mystery about whether China (PRC) exported its nuclear technologies at that time. Through unpacking three sets of contemporaneous Chinese archival materials, this article unveils the details of Indonesian research and military personnel visits to PRC nuclear sites and the nature of bilateral political and academic discussions on nuclear weapons. It argues that, while there was no movement of nuclear fuel or hardware between the two countries, Sino-Indonesian exchanges reveal the fluidity of individual political players’ ideologies (including those of left-leaning politicians, anticommunists, and neutralists), the complexity of bilateral relations, and the paradoxical quality of Third World solidarity in the atomic age. Many of the military and technical experts who approached Beijing for nuclear aid peacefully transitioned into the Suharto era and achieved personal success, quite unlike the experiences of “pro-China” Indonesian politicians who weren’t favorably associated with the nuclear program. Ideological fissures persisted between the two countries even when they shared substantial mutual interests in the short term. But those schisms sometimes appeared to be invisible to the United States and Soviet Union, which at the time were anxious to rein in potential nuclear proliferators in the Third World, and particularly in the Asia-Pacific region against the backdrop of the ongoing conflict in Vietnam.